Exploring factors for the introduction and implementation of quality assurance systems in selected higher education institutions in Tanzania - Evaristo Andreas Mtitu (Cogent Education)
This article investigates factors for the introduction and implementation of quality assurance (QA) systems in selected higher education institutions (HEIs) in Tanzania. With the global emphasis on educational quality and the increasing demand for accountability in higher education. Tanzanian universities face the critical task of developing and maintaining effective QA systems. Thus, this study contributes to broader discourse on QA in higher education by providing a contextual analysis of Tanzanian universities, offering practical solutions for other institutions facing similar challenges. The study employs a mixed-methods approach, combining quantitative surveys and qualitative interviews with key stakeholders, including university administrators, faculty members and students, across four universities. The findings reveal diverse levels of agreement among respondents regarding ways in which QA systems were introduced to ensure quality education systems. with some institutions demonstrating strong consensus. Key factors contributing to the introduction of QA were regulatory requirement, stakeholders’ consultations, and students’ learning processes. Moreover, QA operations included programme advertisement and marketing; students’ admission, assessment and academic programmes among others.. The article proposes the need for consistent policy application, improved communication, adequate resource allocation, fostering a culture of quality and addressing structural challenges to adopting these strategies, HEIs in Tanzania can better meet international standards of quality and accountability, thereby enhancing the educational experiences and outcomes for their students.